1992
DOI: 10.1007/bf00431250
|View full text |Cite
|
Sign up to set email alerts
|

Genomic mapping within the albino-deletion complex using individual early postimplantation mouse embryos

Abstract: Sensitive methods for analysis of DNA from limited amounts of tissue are often difficult, error prone, and time consuming. Here, we describe a procedure for molecular analysis of individual early postimplantation mouse embryos by Southern analysis. The procedure involves embedding single embryos in agarose before lysing and deproteinizing in situ. The embedded DNA can be digested with restriction enzymes and analyzed by standard Southern-blotting procedures. The procedure is sensitive enough to detect single-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

1992
1992
1995
1995

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Recently, embryos homozygous for the c e~ deletion, a member of the original Di group of c deletions (Russell et al 1982), were found to exhibit a phenotype identical to that found in embryos homozygous for c zzDsD (Sharan et al 1992). c 2~ does not extend as far as D7CwrllD, the locus defined by the distal breakpoint of the c re)so deletion (Sharan et al 1992).…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…Recently, embryos homozygous for the c e~ deletion, a member of the original Di group of c deletions (Russell et al 1982), were found to exhibit a phenotype identical to that found in embryos homozygous for c zzDsD (Sharan et al 1992). c 2~ does not extend as far as D7CwrllD, the locus defined by the distal breakpoint of the c re)so deletion (Sharan et al 1992).…”
Section: Introductionmentioning
confidence: 97%
“…Recently, embryos homozygous for the c e~ deletion, a member of the original Di group of c deletions (Russell et al 1982), were found to exhibit a phenotype identical to that found in embryos homozygous for c zzDsD (Sharan et al 1992). c 2~ does not extend as far as D7CwrllD, the locus defined by the distal breakpoint of the c re)so deletion (Sharan et al 1992). Mice homozygous for either the c TM or c zz2K deletions, which both delete the segment from Fah to Mod-2, progress completely through development but die shortly after birth (Gluecksohn-Waelsch 1979;Russell et al 1982).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations